Ideologi Anti-Barat dan Musik Ngak-Ngik-Ngok: Politik Kebudayaan dan Regulasi Musik Era Soekarno - Arjaya, Derta; Nurullita, Hervina; Afiyanto, Hendra (Jurnal Sejarah Citra Lekha, 2025)
This study examines Soekarno’s perspective on Western influences during the 1950s–1960s and its impact on the development of music in Indonesia. The study addresses two main questions: first, how did Soekarno view the West during his presidency; and second, how did this view affect the trajectory of Indonesian music? Employing the historical method, the research integrates heuristics, source criticism, interpretation, and historiography to analyze primary and secondary sources. The findings reveal that Soekarno perceived the West as a political and cultural threat, frequently labeling it as “Nekolim” (neo-colonialism and imperialism). He viewed Western music not merely as a foreign art form but as a vehicle of cultural domination that undermined the revolutionary ideals and national identity of Indonesia. As a result, Western-influenced music was subject to prohibition, exemplified by the banning of the ngak-ngik-ngok music, which was considered detrimental to Indonesian cultural values. Soekarno promoted policies aimed at fostering music that aligned with nationalist and revolutionary principles, thereby restricting the development and performance of Western styles within the country. This study concludes that Soekarno’s ideological stance significantly shaped the evolution of Indonesian music during his era. By enforcing cultural policies rooted in nationalism, he directly influenced which musical forms could flourish, emphasizing the creation and preservation of a distinctly Indonesian musical identity